THE EFFECT OF PRODUCT QUALITY AND PRICE ON PURCHASE DECISIONS IN SOURFELLY CUSTOM CAKERY, WEST JAKARTA - Alfian, Renata; Dewantara, Yudhiet Fajar (Journal of Business And Entrepreneurship, 2020)
The development of the patisserie industry, which is increasing in demand, causes competition in this industry to be tighter and have more value than other competitors. In this study, researchers examined Sourfelly Custom Cakery as one of the businesses in patisserie by examining the effect of product quality and price on purchasing decisions. The type of research method used is quantitative research methods with causal associative research types. This study, involving 48 respondents using a simple random sampling approach, is aimed at Sourfelly Custom Cakery consumers. The data analysis technique used is multiple linear regression with t-test, F-test, and determination coefficient, assisted by the SPSS24 software program. The results prove that the product quality partially does not significantly influence the purchase decision, and the price partially has a significant effect on the purchase decision. Also, product quality and price simultaneously influence purchasing decisions. From this study also obtained several suggestions and conclusions that should be used for Sourfelly Custom Cakery as input to be able to improve product quality and establish a better pricing strategy to improve consumer purchasing decisions.